Proceedings of the Fifth Symposium of Risk Analysis and Risk Management in Western China (WRARM 2017) 2017
DOI: 10.2991/wrarm-17.2017.20
|View full text |Cite
|
Sign up to set email alerts
|

Financial Situation of Listed Companies in Pharmaceutical Industry

Abstract: This paper studies the financial risks of listed companies in China's pharmaceutical industry by means of qualitative research and quantitative research. Based on the financial data of Guizhou bailing pharmaceutical co, ltd. in 2015 and 2016. The empirical analysis shows that: Based on the fuzzy comprehensive evaluation method, the financial situation analysis of the listed companies in the pharmaceutical industry is feasible in the first year and the year of T. The financial status of listed companies in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Due to the strict vetting procedures of banks and other financial institutions for loans to start-ups, coupled with the high threshold for firms to issue bonds in the market, start-ups may face higher interest rates for loans than larger firms or firms with superior credit when using bank financing, resulting in a situation where bank financing reduce the profitability of start-ups (Yin, Jianzhong, and Jundan Pi, 2017). But the use of mercantile credit instead increases the profitability of startups because mercantile credit usually occurs in commodity transactions and has a low financing threshold and no interest payment compared to other financing methods, making financing costs lower (Yan, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the strict vetting procedures of banks and other financial institutions for loans to start-ups, coupled with the high threshold for firms to issue bonds in the market, start-ups may face higher interest rates for loans than larger firms or firms with superior credit when using bank financing, resulting in a situation where bank financing reduce the profitability of start-ups (Yin, Jianzhong, and Jundan Pi, 2017). But the use of mercantile credit instead increases the profitability of startups because mercantile credit usually occurs in commodity transactions and has a low financing threshold and no interest payment compared to other financing methods, making financing costs lower (Yan, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Chen and Zou (2019) used a regression analysis with agricultural companies as a research sample and obtained the conclusion that the long-term debt ratio of public agricultural companies is positively related to corporate financial performance, while the short-term debt ratio is negatively related to corporate financial performance. Yan (2017) analyzed five different modes of transport in the transport industry and found that, except for the significant relationship between mercantile credit ratio and financial performance, the total debt financing ratio, long-term debt ratio, short-term debt ratio, bank financing ratio and financial performance of public companies in the transport industry were negatively related. Xu (2019) found that during the maturity period of the development of listed companies in the wholesale and retail sector, long-term debt ratio has a positive effect on financial performance improvement, while short-term debt ratio has a negative effect.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Although the relevant regulatory authorities have issued a lot of laws and regulations, in real life, such problems occur from time to time, and it is difficult to stop them. According to the statistical results, in 2020 and 2021, 22 listed companies were imposed administrative punishment by the China Securities Regulatory Commission (hereinafter referred to as the CSRC) for financial fraud, which had a negative impact on investors, the capital market, and society [3].…”
Section: Introductionmentioning
confidence: 99%